Development and characterization of walnut/vinyl ester filled homogeneous and their functionally graded composites. (2021) - Raman, Abhishek; Kushwah, Kamlesh; Goyal, Sanjay; Gangil, Brijesh; Ranakoti, Lalit
Abstract: The work carried in the present study deals with the physical and mechanical characterization of walnut filled-vinyl ester composite prepared by gravity die casting and centrifugal casting (functionally graded materials). Among the physical and mechanical properties, void content, hardness, flexural strength, and impact energy in the case of functionally graded materials (FGMs) are found to boost with the increase in filler content. In contrast, tensile strength was found to deteriorate for FGMs as compared to homogeneous and neat composites. Pin-on-disc (POD) machine was used to evluatethe sliding wear performance of the fabricated composites of both types under specific humidity and thermal conditions The overall result shows that the wear rate of FGM composites is comparatively lower than GDC composites.